The “simple” view of learning from illustrated texts and videos - Haavisto, Mikko; Lepola, Janne; Jaakkola, Tomi (Elsevier, 2026)
Background: The recent decline in children's reading skills in OECD regions poses challenges for traditional text-based learning. At the same time, teachers increasingly use videos in primary instruction. Despite these developments, limited research exists on how children's reading skills influence learning from videos versus illustrated texts in primary school classrooms.
Aims: This study investigates the roles of decoding ability and reading comprehension in learning from videos versus illustrated texts among fifth and sixth graders. It aims to determine to what degree these factors influence learning outcomes and cognitive load.
Sample: 109 children from grades 5–6 across three public primary schools.
Methods: In a within-subjects experiment, participants studied both illustrated texts and videos on two science topics. Their performance was measured through pre-, post-, and delayed tests. Mixed-effects models assessed the effect of modality and reading skills on learning outcomes and cognitive load.
Results: The children performed significantly better when learning from videos compared to illustrated texts, demonstrating higher delayed retention and lower cognitive load. There was no difference in retrieval from materials or transfer. Decoding ability and reading comprehension positively predicted learning outcomes and interacted with modality: the retention benefits of videos were more pronounced in children with lower reading skills than in those with higher reading skills.
Conclusions: The results indicate that videos are beneficial to most children across reading skill levels, especially those with weaker reading skills. This suggests that incorporating videos into primary school science instruction supports diverse learning needs associated with weaker reading skills.